Crimes culposos de trânsito - Martins, Rodney Charles Muller (2010)
This paper examines the unintentional traffic crimes and their punishments and checks whether these legal features are efficient in fighting the high rate of accidents involving motor vehicles, a consequence of the needed speedy transportation demanded by the global societies members. Along the first lines, intentional and unintentional crimes are explained and differentiated along with a detailed approach of their historic evolution. Another type of crime, actually this paper s main theme, demanded a special chapter, where its historic origins are fully discussed before the world s main cultures and also the most relevant theories which explain why they are in fact punished and all the needed elements to appropriately characterize them. Along the traffic crimes' analysis and comments were presented their specific criminal types and the focus has been upon the unintentional kind and all the related enforcement measures, legal and non-legal. Regarding the presented chapters, this study intends to offer solutions which can help to diminish it or, at least, prevent its increase between the limits of the present legislation